Pengelolaan Warisan Budaya Bangka: Inkonsistensi Kebijakan, Regulasi dan Partisipasi Publik - Iskandar Zulkarnain (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2015)
This study aimed to describe government policy in managing the cultural heritage as a basis for legal regulation spawned cultural heritage management can strengthen the identity. This study uses qualitative policy analysis. Policy analysis seeks to influence the policy-making process